Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1111/jcpp.12922
|View full text |Cite
|
Sign up to set email alerts
|

A neural biomarker, the error‐related negativity, predicts the first onset of generalized anxiety disorder in a large sample of adolescent females

Abstract: This study provides evidence for the utility of the ERN as a biomarker of risk for GAD during a key developmental period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
51
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 59 publications
7
51
0
Order By: Relevance
“…Future work should establish norms for the ERN that can be used to identify who is most at risk for anxiety during different stages of development. Additionally, future studies should examine what factors may influence or shape the ERN during specific developmental periods – for example, some work suggests harsh parenting styles may increase the ERN in offspring (Brooker & Buss, 2014; Meyer et al, 2014). Moreover, given that the ERN indexes risk for anxiety, future work should examine whether the ERN may be a viable target for treatment and prevention efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Future work should establish norms for the ERN that can be used to identify who is most at risk for anxiety during different stages of development. Additionally, future studies should examine what factors may influence or shape the ERN during specific developmental periods – for example, some work suggests harsh parenting styles may increase the ERN in offspring (Brooker & Buss, 2014; Meyer et al, 2014). Moreover, given that the ERN indexes risk for anxiety, future work should examine whether the ERN may be a viable target for treatment and prevention efforts.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that individuals at familial risk for anxiety disorders also show increased ERN amplitudes. Additional support for increased ERN as a candidate endophenotype for anxiety comes from studies suggesting that ERN magnitude could be used to predict the onset of GAD (Meyer et al, ), social anxiety (Lahat et al, ), and anxiety symptoms collapsed across different DSM categories (McDermott et al, ; Meyer et al, ; Meyer, Hajcak et al, ). Collectively, these results support the idea that increased ERN amplitudes represent a shared endophenotype for OCD and anxiety (Olvet & Hajcak, ; Riesel et al, , in press).…”
Section: Section 2: Enhanced Neural Error Signals As Endophenotype Fomentioning
confidence: 99%
“…Importantly, the clinical relevance of error‐related brain activity is supported by studies demonstrating its predictive validity for the onset of symptoms across various mental disorders (Anokhin & Golosheykin, ; Lahat et al, ; Meyer, Hajcak et al, ; Meyer et al, ). In longitudinal studies, ERN predicted the onset of anxiety symptoms in children and adolescents (Lahat et al, ; Lamm et al, ; Meyer, Hajcak et al, ; Meyer et al, ) and the development of symptoms in response to critical life events such as a natural disaster (Meyer et al, ). Further, in preschool‐aged individuals, observed hyperactive performance monitoring at the behavioral level predicted the onset of OCD and reduced ACC volume over 12 years (Gilbert, Barclay, Tillman, Barch, & Luby, ).…”
Section: Section 3: Clinical Implications and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ERN is a sharp, negative deflection in the event‐related potential (ERP) waveform that occurs shortly after individuals make mistakes (Falkenstein, Hohnsbein, Hoormann, & Blanke, ; Gehring, Goss, Coles, Meyer, & Donchin, ) and is generated in the anterior cingulate cortex (ACC)—a region of the brain that integrates information about pain, threat, and punishment to modify behavioral output (Shackman et al, ). An increased ERN has been found in individuals with anxiety‐related traits (e.g., worry, punishment sensitivity) and symptoms in over 45 studies to date (see meta‐analysis: Moser, Moran, Schroder, Donnellan, & Yeung, ), and we have recently found that an increased ERN predicts the onset of new anxiety disorders in children—even when controlling for baseline anxiety symptoms and other risk factors (Meyer, Hajcak, Torpey‐Newman, Kujawa, & Klein, ; Meyer, Nelson, Perlman, Klein, & Kotov, Under Review). Considering that the ERN consistently relates to anxiety and similar traits, and has good psychometric properties across development (Meyer, Bress, & Proudfit, ), it is an important neural measure for studying the development of anxious processes.…”
Section: Introductionmentioning
confidence: 99%